The role of maternal infection in preterm birth: evidence from the Brazilian Multicentre Study on Preterm Birth (EMIP) - Tedesco, Ricardo P. (2020)
OBJECTIVES: Evidence suggests that infection or inflammation is a major contributor to early spontaneous preterm birth (sPTB). Therefore, this study aimed to investigate the development and causes of maternal infection associated with maternal and neonatal outcomes in women with sPTB. METHODS: This was a secondary analysis of a multicenter cross-sectional study with a nested case–control component, the Brazilian Multicentre Study on Preterm Birth (EMIP), conducted from April 2011 to July 2012 in 20 Brazilian referral obstetric hospitals. Women with preterm birth (PTB) and their neonates were enrolled. In this analysis, 2,682 women undergoing spontaneous preterm labor and premature pre-labor rupture of membranes were included. Two groups were identified based on self-reports or prenatal or hospital records: women with at least one infection factor and women without any maternal infection (vulvovaginitis, urinary tract infection, or dental infection). A bivariate analysis was performed to identify potential individual risk factors for PTB. The odds ratios (ORs) with their respective 95% confidence intervals were calculated. RESULTS: The majority of women with sPTB fulfilled at least one criterion for the identification of maternal infection (65.9%), and more than half reported having urinary tract infection during pregnancy. Approximately 9.6% of women with PTB and maternal infection were classified as having periodontal infection only. Apart from the presence of a partner, which was more common among women with infectious diseases (p=0.026; OR, 1.28 [1.03–1.59]), other variables did not show any significant difference between groups. CONCLUSION: Maternal infection was highly prevalent in all cases of sPTBs, although it was not clearly associated with the type of PTB, gestational age, or any adverse neonatal outcomes.